Histopathological in Gills, Hepatopancreas and Gut of White Shrimp (Litopenaeus Vannamei) Infected White Feces Disease (WFD) - Jefri Anjaini; Mohamad Fadjar; Sri Andayani; Ivana Agustin; Ilham Bayu (Research Journal of Life Science, 2018)
White Feces Disease which is the presence of white feces floating on the surface of the water. Physical disruption of White Feces Disease attacked by exocytes becoming soft. the cause of white defect disease (WFD) is a decrease in environmental quality such as salinity, DO and ammonia. white feces disease is associated with gregarine protozoa in the Apicomplexa phylum. Gregarine parasitic infection from the type of nematopsis that was interacted with Vibrio and Vibrio type bacteria found in white shrimp (Litopenaeus vannamei) which was attacked by white impurities was V. harveyi. This study aims to analyze the presence of gregarine protozoa in the gills, intestines and hepatopancreas of white shrimp infected with White Feces Disease. The method used in this research is descriptive method. Histopathological results showed that there were protozoa (Gregarine) in the intestine, hepatopancreas and gills of white shrimp infected with WFS in 3 different locations and found Aggregated Transformed Microvilli (ATM) that resembled gregarine.